The Relationship Between Students Listening to English Song Habit and Their Ability to Speak English Among Second Semester Students at English Department of Universitas Bhinneka PGRI - Oscar Andi Prastyo; Ayu Rizki Septiana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to determine: the significant relationship between students' habit of listening to English songs and their ability to speak English among second semester students at English education Department of Universitas Bhinneka PGRI Tulungagung in the academic year 2023/2024. The researcher used quantitative research. The study used the correlational design. The populations in this research were second semester students at Study Program of English Education at Universitas Bhinneka PGRI in the academic year of 2023/2024 which consist of 20 students. The researcher used questionnaire and speaking test as the techniques to collect the data for the research. The result of the analysis in this study show that Pearson Correlation was 0.423. It means that the relationship between listening to English song habits and their ability to speak English was in moderate correlation. Further, the significance value of hypothesis testing is 0.063 which is higher than 0.05. Thus, it can be concluded that Ho is accepted and Ha was rejected. In the other words, there is no significant correlation between listening to English song habits and their ability to speak English.